2t+1/9-6t=289/9

Simple and best practice solution for 2t+1/9-6t=289/9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2t+1/9-6t=289/9 equation:


t in (-oo:+oo)

2*t-(6*t)+1/9 = 289/9 // - 289/9

2*t-(6*t)+1/9-(289/9) = 0

2*t-6*t+1/9-289/9 = 0

-4*t-32 = 0 // + 32

-4*t = 32 // : -4

t = 32/(-4)

t = -8

t = -8

See similar equations:

| k+1/4+4k=161/4 | | -1/4+7d-d=191/4 | | 7/9+4x+3/4x=-229/72 | | -2x-4y=-1 | | 7+a-6a=-48 | | 3+5k+3k=91 | | -241/7=5w+3/7w+9 | | -1/3+4/5m+5/6m=142/15 | | 4/5+5d-3d=94/5 | | 6/7=5/7k+6/7k+4 | | 6n+1+4/5n=-267/5 | | 4x^2+16y^2+16x=48 | | 62/9=5d+2d+3 | | 2k+10+3/5k=602/55 | | -2/7-6a-2/3a=-286/21 | | 6a-3-a=2 | | -17/3=w-3w+1/3 | | 1/5k+4/5+1/6k=4/5 | | -w+1+5w=49 | | 2/5x-1-3/5x=-53/50 | | 3=x/26+6 | | 1/3+3x+5x=97/3 | | -7/9+1/2b+4/5b=-187/90 | | x-5/6=1/10 | | -a+2+7a=6 | | 4+1/2m-m=79/18 | | 7m+1/5+1/7m=507/35 | | -4/5-2w+1/4w=-83/60 | | -1/2+2/5t-t=11/2 | | -3/8+1/3m+7m=871/24 | | -6b+2/7-6b=-82/7 | | 323/28=4a+5/7a+8 |

Equations solver categories